The art of love : bimillennial essays on Ovid's Ars amatoria and Remedia amoris - Gibson, Roy K.; Green, Steven J., 1973-; Sharrock, Alison (Oxford University Press, 2006)
"The Art of Love celebrates the bi-millennium of Ovid's cycle of sophisticated and subversive didactic poems on love, traditionally assumed to have been brought to completion around AD 2. Ars Amatoria (The Art of Love) and Remedia Amoris (Cures for Love), which purport to teach young Roman men and women how to be good lovers, were partly responsible for the poet's exile from Rome under the emperor Augustus. None the less they exerted great influence over ancient and later love poetry. This is the first collection in English devoted to the poems, and brings together many of the leading figures in the field of Latin literature and Ovidian studies from the British Isles, Germany, Italy, and the United States. It offers a range of perspectives on the poetics, politics, and erotics of the poems, beginning with a critical survey of recent research, and concluding with papers on the ancient, medieval, and modern reception of the poems."--Publisher's description.